Increasing the efficiency of forging tools by thermal diffusion boronizing - Željko Stojanović; Sanja Stanisavljev; Spasoje Erić; Mića Đurđev (Zaštita Materijala)
In this paper is given a review of literature data about research of influence thermal diffusion boronizing on increasing of working life and quality of forging dies. Service life of tools depends mainly of the surface of material, and it is important that the surface has features such as: corrosion resistance, wear resistance and resistance to oxidation. In order to improve the surface properties some surface treatments with order to protect the surface and improve performance of materials are applied. Service life of steel dies for forging processing, which is limited by wear, can be increased by various surface treatments in which the surface layer alloyed with nitrogen, carbon or boron. These diffusion coatings consist of metal or nonmetal diffusion in the base material at high temperatures. In searching for an alternative to conventional methods, the authors came to the conclusion that experiences in boronizing of a wide range of tools for forging processing showed that the operating stability of the parts subjected to this process, increased from two to ten times.